2012
DOI: 10.3791/3918
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Isolation of Slow-Dividing Cells in Human Glioblastoma Using Carboxy Fluorescein Succinimidyl Ester (CFSE)

Abstract: Tumor heterogeneity represents a fundamental feature supporting tumor robustness and presents a central obstacle to the development of therapeutic strategies 1 . To overcome the issue of tumor heterogeneity, it is essential to develop assays and tools enabling phenotypic, (epi)genetic and functional identification and characterization of tumor subpopulations that drive specific disease pathologies and represent clinically relevant targets. It is now well established that tumors exhibit distinct sub-fractions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…Following the last passage, neurospheres were labeled with carboxyfluorescein succinimidyl ester (CFSE) dye and treated with 4OH‐Tam. Dissociated cells were incubated with anti‐CD15 antibody for fluorescence‐activated cell sorting (FACS) .…”
Section: Methodsmentioning
confidence: 99%
“…Following the last passage, neurospheres were labeled with carboxyfluorescein succinimidyl ester (CFSE) dye and treated with 4OH‐Tam. Dissociated cells were incubated with anti‐CD15 antibody for fluorescence‐activated cell sorting (FACS) .…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have found that CFSE labeling can be used to identify and isolate a slow proliferating population of cells from glioblastomas. These dye-retaining brain tumor cell populations are enriched in CSCs, and the progeny that differentiate from these labelretaining cells exhibit all the pathological features of the primary disease [164,165]. Kamohara et al used Hoechst 33342 and Pyronin Y to sort Huh7 cells into G0, G1, and G2/M fractions by FACS.…”
Section: Cancer Cell Divisionmentioning
confidence: 99%
“…Due to the low sensitivity of HEY1 to cisplatin at baseline, animals were treated with 2 daily doses of high-dose paclitaxel (16 mg/kg). While control tumors demonstrate a complete response to chemotherapy, tumors in which IcNFATC4 expression was transiently induced demonstrated growth arrest in response to doxycycline, and then ~8 days after 13 doxycycline discontinuation, tumors resumed normal growth without any evidence of response to therapy (p<0.001) ( Fig. 6e).…”
Section: Cnfatc4 Expression Suppresses Tumor Growth and Drives Chemotmentioning
confidence: 97%
“…To agnostically determine if NFATC4 was enriched in slower proliferating cells, we used evaluated NFATC4 expression in slowly proliferating/vital dye retaining cells 13 in multiple ovarian cancer cell lines. Slow growing/dye retaining cells (Bright), demonstrated a significant enrichment for NFATC4 compared to the fast-growing cells (dim) in all four cell lines tested (HEY1 p<0.05, OVSAHO p<0.001, CaOV3 p<0.01, COV362 p<0.05) ( Fig.…”
Section: Nfatc4 Is Mrna and Activity Are Enriched In A Population Of mentioning
confidence: 99%